The relative and interactive effects of urinary multiple metals exposure on hyperuricemia among urban elderly in China - Huang, Chao; Gao, Erwei; Xiao, Feng; Wu, Qiongzhen; Liu, Wei; Luo, Yi; Ren, Xiaohu; Chen, Xiao; He, Kaiwu; Huang, Haiyan; Sun, Qian; Wu, Desheng; et al. (Frontiers in Public Health, 2023)
Objective: Independent and interactive effects of multiple metals levels in urine on the risk of hyperuricemia (HUA) in the elderly were investigated. Methods: A total of 6,508 individuals from the baseline population of the Shenzhen Aging Related Disorder Cohort were included in this study. We detected urinary concentrations of 24 metals using inductively coupled plasma mass spectrometry, fitted unconditional logistic regression models and the least absolute shrinkage and selection operator regression models for selection of metals as well as unconditional stepwise logistic regression models and restricted cubic spline logistic regression models for assessing the associations of urinary metals and HUA risk, and finally applied generalized linear models to determine the interaction with urinary metals on the risk of HUA. Results: Unconditional stepwise logistic regression models showed the association between urinary vanadium, iron, nickel, zinc or arsenic and HUA risk (all P < 0.05). We reveled a negative linear dose-response relationship of urinary iron levels with HUA risk (Poverall < 0.001, Pnonliner = 0.682), and a positive linear dose-response relationship of urinary zinc levels with HUA risk (Poverall < 0.001, Pnonliner = 0.513) and the relation of additive interaction of urinary low-iron and high-zinc on HUA risk (RERI = 0.31, 95%CI: 0.03-0.59; AP = 0.18, 95%CI: 0.02-0.34; S = 1.76, 95%CI: 1.69-3.49). Conclusion: Urinary vanadium, iron, nickel, zinc or arsenic levels were associated with HUA risk, the additive interaction of low-iron (< 78.56 μg/L) and high-zinc ( 385.39 μg/L) my lead to a higher risk of HUA.